MIGRASI TENAGA KERJA INDONESIA KE LUAR NEGERI MENGGUNAKAN COST BENEFIT ANALYSIS (Studi di Kabupaten Malang) - Mohammad Rizal (Universitas Negeri Malang, 2014)
Malang regency is one of greatest special places of Indonesian migrant workers of Indonesia which contributing big number enough of Indonesian migrant workers. The research is aimed to know what kinds of matters faced by Indonesian migrant workers of Malang Regency when they are in pre-placement time, placement time, and after placement time, know comparison of cost benefit had been had by Indonesian migrant workers of Malang Regency and the comparison of cost benefit between the destination countries. The outcomes of the research shows that based on the calculation yields of Cost Benefit Analysis of 15 ex-Indonesian migrant workers are wholly fulfilled the requirements to be prioritized, since in the Net Present Benefit (NPB) Method and also by Benefit Cost Ratio Method (BCR) all shows that the calculation yields are feasible to operate. Keywords: Migration, Indonesian Manpower, Cost Benefit Analysis